2011
DOI: 10.4049/jimmunol.0903794
|View full text |Cite
|
Sign up to set email alerts
|

The Airway Antigen Sampling System: Respiratory M Cells as an Alternative Gateway for Inhaled Antigens

Abstract: In this study, we demonstrated a new airway Ag sampling site by analyzing tissue sections of the murine nasal passages. We revealed the presence of respiratory M cells, which had the ability to take up OVA and recombinant Salmonella typhimurium expressing GFP, in the turbinates covered with single-layer epithelium. These M cells were also capable of taking up respiratory pathogen group A Streptococcus after nasal challenge. Inhibitor of DNA binding/differentiation 2 (Id2)-deficient mice, which are deficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…Although these NALT M cells resemble Peyer's patch M cells in their basic morphology and antigen sampling properties, it is not yet known to what extent they express the same specific markers that are characteristically expressed by Peyer's patch M cells and whether their differentiation from epithelial stem cells is regulated in a similar manner. In addition to the M cells associated with the FAE above the NALT, the upper respiratory tract of mice also includes an additional class of NALT-independent respiratory M cells positioned within the respiratory epithelium away from any lymphoid aggregates (Kim et al, 2011).…”
Section: Cells In Other Mucosa-associated Lymphoid Tissuesmentioning
confidence: 99%
“…Although these NALT M cells resemble Peyer's patch M cells in their basic morphology and antigen sampling properties, it is not yet known to what extent they express the same specific markers that are characteristically expressed by Peyer's patch M cells and whether their differentiation from epithelial stem cells is regulated in a similar manner. In addition to the M cells associated with the FAE above the NALT, the upper respiratory tract of mice also includes an additional class of NALT-independent respiratory M cells positioned within the respiratory epithelium away from any lymphoid aggregates (Kim et al, 2011).…”
Section: Cells In Other Mucosa-associated Lymphoid Tissuesmentioning
confidence: 99%
“…The morphology, topographical proximity to intraepithelial lymphocytes, and ability of M cells of NALT to take up luminal antigens are similar to those of intestinal M cells (Gebert et al 1999). Histochemically, the M cells of NALT have been identified by the expression of cytokeratin 8, 18, 20, and vimentin in the rabbit palatine tonsil (Carapelli et al 2004;Gebert et al 1995;Jepson et al 1992); the expression of clusterin and class II "-tubulin in the human Waldeyer's ring (Lee et al 2010;Verbrugghe et al 2008); and 5 affinity to Ulex europaeus agglutinin I (UEA-I) lectin in murine and rat NALT (Jeong et al 1999; Kim et al 2011). Recent studies identified various unique molecules expressed in the M cells of Peyer's patches.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of TLR2 or TLR4 ligands into the lower airways carries the potential danger of exacerbating lower airway inflammation by promoting monocytic/neutrophilic inflammation (22). Alternatively, the nasal mucosa is populated by lymphoid tissues (23), as well as the recently described M cells (24), which can serve as effective inductive sites for immune responses, while minimizing exposure of the lower airways to TLR ligands. Thus, we assessed the immunomodulatory potential of nasal application of Protollin as an adjuvant in intranasal immunotherapy of lower airway disease, in a murine model of birch pollen allergic asthma, and focused on the changes in CD4 + T cell responses induced by Protollin in vivo via the nasal mucosa.…”
mentioning
confidence: 99%